UZBEKISTAN'S ACCESSION TO THE WORLD TRADE ORGANIZATION (WTO): CHALLENGES AND SOLUTIONS (European Journal of Economics, Finance and Business Development, 2025)
This article analyzes Uzbekistan's process of joining the World Trade Organization (WTO). The main challenges and their solutions are examined within the framework of economic, legal, social, and political aspects. Additionally, the anticipated benefits and strategic importance of WTO membership for our country are discussed.